Factors influencing the information behaviour of doctors and nurses in South Africa's Eastern Cape, Mpumalanga, Limpopo and Northern Cape provinces: a survey study protocol. Issue 12 (13th December 2022) - Chitha, Nombulelo; Mabunda, Sikhumbuzo A; Essel, Vivien; Funani, Itumeleng; Godlimpi, Lizo; Swartbooi, Buyiswa; Mnyaka, Onke; Thabede, Jahman; Tshabalala, Ruth; Chitha, Wezile
Abstract : Introduction: Information is a prerequisite for quality healthcare service. Health professionals play a key role in the health system as they jointly have the responsibility of looking after patients everyday. Failure to use evidence in medicine may lead to medical errors such as incorrect diagnosis and/or mismanagement. Health professionals with access to quality health information can improve health services. This study focuses on the information behaviour of doctors and nurses whose role involves direct patient care. Methods and analysis: This study will employ a quantitative approach using a cross-sectional survey design. Simple random sampling will be used to identify the provinces and hospitals. Stratified random sampling will be used to select doctors and nurses to whom a validated questionnaire will be administered. The study will use a structured self-administered questionnaire. Data collection will be carried out at Nelson Mandela Academic Hospital, Witbank Hospital, Pietersburg Hospital and Robert Mangaliso Hospital, respectively. Questionnaires are distributed to health professionals in one of two ways. First, by emailing an editable Microsoft word document (questionnaire) to the health professionals to complete and send back. Second, by sharing with the health professionals through WhatsApp or email, an online version of the questionnaire that has been created on Google Forms. Data collection process is scheduled to commence on 14 March 2022 and is expected to end on the 15 September 2022. Ethics and dissemination: Ethical approval was obtained from the University of the Witwatersrand Human Research Ethics Committee (reference: M211013) and Walter Sisulu University Human Research Ethics and Biosafety Committee (reference: 099/2021). Permission to access the health facilities was approved by the Provincial Health Research Committees of the Eastern Cape, Limpopo, Mpumalanga and Northern Cape. Finally, results will be shared with all key stakeholders, including hospital management, clinical staff, through public presentation and direct engagements with stakeholders.